2013
DOI: 10.1097/aap.0b013e318277a870
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Loss of Neural Function After Interscalene Plexus Blockade May Be Caused by Epidural Spread of Local Anesthetics

Abstract: Contralateral blockade after ultrasound-guided interscalene injection of local anesthetics is very likely to be the effect of epidural spread. Future in vivo studies are needed to understand the implications of needle location and volume on epidural spread in interscalene blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…A prospective power analysis was performed using previous data from the authors' cadaveric study, suggesting a difference of 60% in epidural spread during use of a small vs a large volume of radiopaque contrast agent. 8 In order to detect a difference of 60% or more, a sample size of 12 patients per group would be needed to achieve a power of 81% with a two-sided Fisher's exact test with a significance level of 5%. A total of 15 patients per group was planned in order to allow for dropouts attributable to technical failure or protocol deviations and to account for more subtle differences between groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective power analysis was performed using previous data from the authors' cadaveric study, suggesting a difference of 60% in epidural spread during use of a small vs a large volume of radiopaque contrast agent. 8 In order to detect a difference of 60% or more, a sample size of 12 patients per group would be needed to achieve a power of 81% with a two-sided Fisher's exact test with a significance level of 5%. A total of 15 patients per group was planned in order to allow for dropouts attributable to technical failure or protocol deviations and to account for more subtle differences between groups.…”
Section: Methodsmentioning
confidence: 99%
“…Our group previously performed a cadaveric study of ISB followed by computed tomography to assess epidural spread using progressively higher volumes of contrast dye. 8 Higher volumes were associated with a significantly higher incidence of ipsilateral and contralateral epidural spread.…”
mentioning
confidence: 94%
“…Furthermore, imaging or dissection of cadavers has shown that ultrasonically guided subepineurial needle placement and injection using the interscalene approach can result in epidural spread of dye. 89,90 Limitations and Future Directions…”
Section: Indirect Effects Of Ugra On Patient Safetymentioning
confidence: 99%
“…107 In addition to potential nerve injury, unintended intraneural injection in the interscalene region has been associated with cadaveric and human evidence of unintended epidural spread of injectate. 89,90 Recent clinical studies suggest that block effectiveness is not compromised by local anesthetic deposition a small distance from the nerve, 108,109 which argues that placing the needle as close as possible to the neural target may not always be beneficial, although these observations are likely to be block specific.…”
Section: Indirect Effects Of Ugra On Patient Safetymentioning
confidence: 99%
“…3 In lateral approach, the needle passes from lateral to medial side at an angle of 20º to skin and parallel to clavicle. Once the needle meets the nerves of brachial plexus, it stimulates muscles contractions or elicits paraesthesia and then reaches to the other structures, hence chances of cervical and thoracic epidural blockade 15 , total spinal anaesthesia 16 , inadvertent injection into the vertebral artery, Horner syndrome and an incidence of recurrent laryngeal nerve blockade are very remote. In our study we encountered no serious sequelae like pleural puncture, pneumothorax or any other cardiorespiratory side effects requiring active intervention, when lateral approach was used.…”
Section: Discussionmentioning
confidence: 99%